Enhancing Self-Control: Counseling Strategies to Mitigate Consumptive Behavior in K-Pop Fans - Sari, Wulan Hertika; Wibowo, Doddy Hendro (Guidance and Counseling Study Program, Pattimura University, 2024)
This study investigates the relationship between self-control and online shopping consumptive behavior among K-Pop fans, focusing on the NCTzen fanbase in Java, Indonesia. Conducted in October 2023, the research collected data from 151 respondents via Google Forms. The study aimed to determine if self-control influences consumptive behavior in online shopping contexts. Descriptive statistics revealed that higher self-control correlates with lower levels of consumptive behavior. The correlation coefficient of -0.198 (p < 0.05) indicates a significant negative relationship. These findings align with previous research, underscoring the critical role of self-control in mitigating excessive spending. The study suggests that counseling programs incorporating self-control enhancement strategies, educational workshops, and parental guidance can effectively reduce impulsive purchases among K-Pop fans. Such interventions are vital for promoting mindful consumption and financial responsibility, especially in the context of online shopping. This study also highlights the need for further research to explore additional factors influencing consumptive behavior in this demographic.